Le Maroc des voyageuses françaises au temps du Protectorat. Une vision (de) colonisatrices ? - Claude Ghiati (Genre & Histoire)
The travel narratives of French women who travelled widely in Morocco during the Protectorate period (1912-1956) vary widely in their style and in their perceptions of a country, which until then was considered unwelcoming and hostile. The literary quality of the resulting works is heterogeneous and most of these narratives are little known. The motivations of these women travellers, their travel condition and means of transportation, as well as the underlying infrastructure changed considerably in these years in response to the public works projects initiated by Field Marshal Lyautey. Some authors present us with ‘impressions’ of landscapes and social living conditions while others adopt a more historical approach in their descriptions that meld contemporary observations with precise information on Moroccan political, social, religious and artistic life. These women’s texts constitute an unusual historical source for this period through their perception of a country in the throes of change, be they completely convinced of the ‘civilizing’ role of France or, on the contrary, staunchly critical of morally shocking attitudes.